Effectiveness of the Responding to Experienced and Anticipated Discrimination (READ) training on reducing stigma for medical students in Tunisia - Lamia Jouini; Uta Ouali; Yosra Zgueb; Emna Bouguira; Ioannis Bakolis; Fethi Nacef; Claire Henderson (PLoS ONE, 2026)
Doctors have been identified as having a crucial role in responding to anticipated and experienced stigma of People with Mental Illness (PWMI). This paper aims to evaluate the effectiveness of the READ (Responding to Experienced and Anticipated Discrimination), an anti-stigma training for medical students, by measuring changes in their knowledge, attitudes, and skills, in responding to patients anticipated and experienced discrimination. The Mental Health Knowledge Schedule (MAKS), the Mental Illness Clinicians’ Attitudes version 2 (MICA2), and an OSCE (Observed Structured Clinical Examination) were used to determine participants’ knowledge, attitudes, and behaviours towards PWMI before and immediately after the training. There was evidence of difference in MICA2 mean total scores in the intervention group were compared to the control group after adjusting for age, gender and MICA baseline mean total scores (MD: −7.88; p < 0.001; 95% CI: −10.23 to −3.96). Moreover, the intervention group was 4.45 times more likely to be scored “pass” in the OSCE compared to the control group (p = 0.046, 95% CI: 1.03 to 19.26) after adjusting for age, gender and OSCE baseline scores. The positive changes in students’ attitudes and skills after the READ training should encourage further research on the causal pathways of this positive relationship.